Theatre for Zheleznogorsk in the architect G. P. Stepanov’s creative activity - Yamaletdinov, Sergey (project baikal, 2023)
23 February 2024 marks the 100th anniversary of the birth of Georgy Petrovich Stepanov (1924-2007), a Soviet and Russian architect, Doctor of Art History, Professor, Honoured Art Worker of the RSFSR, Honorary Member of the Russian Academy of Architecture and Construction Sciences. A major project implemented by G. P. Stepanov was a theatre for Zheleznogorsk in the Krasnoyarsk region. On the basis of the revealed archival data and published materials, the stages of the search for the architectural appearance of the theatre building for the Siberian city are restored. The structure built in neoclassical style influenced the further creative path of the Leningrad architect and the directions of his scientific interests and pedagogical work.